An Early Analysis on the Position and Implementation of the Authoritative Statement of the Shafi‘Ite Madhhab in the Economic Legal Ruling State of Kedah and State of Penang - Dato' Dahaman @ Dahlan, Mohd Akram; Ahmad, Kamarudin; Abdul Hamid, Solahuddin; Mohd Noor, Mohd Murshidi (Global Academic Excellence, 2018)
The authoritative statement of the Shafi‘ite madhhab in the state Islamic religious law has been the basis of a very popular approach among fatwa-authorized bodies in Malaysia. Among the states that laid the foundations of a fatwa based on this approach were the state of Kedah and Penang. There are many fatwas that have been decided in these two states by involving various issues such as faith, worship, marriage, muamalat / economic, social and others. Based on this, a preliminary analysis was undertaken to examine clearly the position of The aauthoritative statement of the Shafi‘ite madhhab and its implementation in fatwa affairs in both states, Kedah and Penang. At the same time, the study also examines the views of other school of thought that have been used to prescribe a fatwa. The results of this initial analysis show the actual situation of the authoritative statement of the Shafi‘ite madhhab in the fatwaauthorized body of the state of Kedah and Penang. The study also explains the position of other schools of thought in the fatwa in both states. Through the analysis of the fatwa text has yielded some clear indication of the basic implementation of The authoritative statement of the Shafi‘ite madhhab in the course of fatwa fixing on various issues arising and formulated